2020
DOI: 10.1038/s41598-020-60756-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between vocal pitch perception and production: a developmental perspective

Abstract: the purpose of this study was to examine the relationships between vocal pitch discrimination abilities and vocal responses to auditory pitch-shifts. Twenty children (6.6-11.7 years) and twenty adults (18-28 years) completed a listening task to determine auditory discrimination abilities to vocal fundamental frequency (f o ) as well as two vocalization tasks in which their perceived f o was modulated in real-time. These pitch-shifts were either unexpected, providing information on auditory feedback control, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
(136 reference statements)
1
19
1
Order By: Relevance
“…Results confirmed that repetitive presentation of F0-shifted vocal stimuli in a constant and predictable manner led to sensorimotor adaptation in both experiments, regardless of the direction of the F0 shift, but overall it was very short-lived once the F0 alteration stopped (and in fact completely absent in the first experiment). These results are partly in line with previous reports 4,5,17,22 . However, we found no link between the magnitude of this adaptation phenomenon and the sensitivity to the error (F0 JND), despite our best effort to optimize the efficiency of the paradigm and inciting participants to believe that the error was self-generated (since it was, precisely, just-noticeable for everyone).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Results confirmed that repetitive presentation of F0-shifted vocal stimuli in a constant and predictable manner led to sensorimotor adaptation in both experiments, regardless of the direction of the F0 shift, but overall it was very short-lived once the F0 alteration stopped (and in fact completely absent in the first experiment). These results are partly in line with previous reports 4,5,17,22 . However, we found no link between the magnitude of this adaptation phenomenon and the sensitivity to the error (F0 JND), despite our best effort to optimize the efficiency of the paradigm and inciting participants to believe that the error was self-generated (since it was, precisely, just-noticeable for everyone).…”
Section: Discussionsupporting
confidence: 93%
“…Inter-subject variability in vowel production led to a wide range of F0 JNDs. Following on previous findings 22,30,39 , we had hypothesized that the inter-speakers' variability in response to F0 perturbation would be due to the broad range of F0 JNDs across different speakers, but we failed to find direct evidence for this hypothesis. Similar investigations have been conducted to directly highlight the mechanistic link between the ability to detect F0 changes and compensate for them.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations